PENGARUH KONSENTRASI GULA DAN CMC (CARBOXYMETHYL CELLULOSE) TERHADAP KADAR AIR DAN SIFAT ORGANOLEPTIK FRUIT LEATHER SIWALAN (BORASSUS FLABELLIFER L.) - Rofida, Aminatur; Ulfa Maulida Farid; Vita Kurnia Utami (Teknologi Hasil Pertanian, Fakultas Teknik, Universitas Annuqayah, 2024)
Siwalan (Borassus flabellifer L.) is one type of palmae that can thrive in dry environments, including Indonesia. Fruit leather can be used as an alternative to utilizing siwalan fruit as an effort to diversify products based on siwalan commodities. One of the shortcomings in fruit leather processing is that good texture and plasticity are difficult to form so that additional ingredients are needed in the process. The purpose of this study was to see the effect of adding sugar and CMC with different concentrations on water content and organoleptic properties including color, taste, aroma and texture attributes of siwalan fruit leather. The study used a completely randomized design (CRD) with 4 treatments including P1 = 10% CMC 0% sugar, P2 = 10% CMC 0.05% sugar, P3 = 15% CMC 1.0% sugar, P4 = 20% CMC 0.05% sugar with each treatment repeated 5 times. The results of the study stated that based on the Duncan test value at the 0.05 level, it can be seen that the addition of different concentrations of CMC and sugar has an effect on the water content of siwalan fruit leather, where P1 (10% CMC 0% sugar) has the highest water content (24.7%) and P3 (15% CMC 1.0% sugar) has the lowest water content value (18.2%). However, the average value of moisture content obtained from the four samples is 21.2% and this figure has met the standards regarding the maximum limit of moisture content of dried sweets. Meanwhile, the results of the assessment of 30 panelists for the organoleptic test stated that there was an effect of the addition of sugar concentration and CMC on texture and taste attributes, but had no effect on color and aroma attributes. And in terms of hedonic or liking, the majority of panelists liked the color of P1, the aroma of P2 and P3, the taste of P4, the texture of P2 and P3.